2004
DOI: 10.1002/pssb.200301919
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting and Vickers hardness properties of ZnO‐added YBCO polycrystalline superconductors

Abstract: The effects of ZnO addition on the microstructure and mechanical properties of the YBCO have been investigated through XRD, SEM, EDX, ac susceptibility measurements and the standard Vickers microhardness testing method. We have prepared the samples by a conventional solid-state reaction method and used an additive method for the YBCO system (0, 0.5 and 1 wt% of ZnO). The orthorhombic strain ∆ = (b -a)/(b + a) increases as the Zn content increases, where a and b are the relevant lattice parameters of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Since hardness is accepted as an inherent material property, it should not vary with indentation load (or size). However, investigations [28][29][30][31] have confirmed that microhardness of various bulk materials were indentation size dependent especially at lower peak loads. In our case, Vickers microhardness values of the MgB 2 specimen also show load dependent behavior (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Since hardness is accepted as an inherent material property, it should not vary with indentation load (or size). However, investigations [28][29][30][31] have confirmed that microhardness of various bulk materials were indentation size dependent especially at lower peak loads. In our case, Vickers microhardness values of the MgB 2 specimen also show load dependent behavior (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Experimental set up for the second harmonic measurements were described in [4,5]. The electronics and the test conditions are explained in [4].…”
Section: Methodsmentioning
confidence: 99%
“…The powders of Y 2 O 3 , BaCO 3 , and CuO were thoroughly mixed in the appropriate amounts and calcined at 940 • C for 24 h. After calcination, the powders were mixed by a grinding machine for 4 h and then pressed into pellets of 13 mm diameter at 375 MPa. The pellets were sintered at 945 • C for 24 h and cooled down to room temperature at a cooling rate of 1 • C/min by flowing oxygen at temperatures between 700 and 250 • C. Details on the microstructure of the sample can be found elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%